Transcending Technologies : Probing Trends and Developments in Telecommunication Systems, Dense Wavelength Division Multipexing (DWDM) for Transmission and Configurafion ”“ A Comprehensive Review and Research Agenda - Mujahidin, Irfan (JAICT, 2025)
Abstract -  In recent years, telecommunication systems have developed so rapidly that it has created a technology trend for transmission and configuration systems. In terms of transmission and configuration, the main trend is to increase network capacity and speed, one of which is with wireless technology. Among the various wireless technologies available, with long-range communication capabilities, increased bandwidth, increased speed, network efficiency, and cost effectiveness, Dense Wavelength Division Multiplexing (DWDM) has emerged as the most popular choice for various applications in transmission systems and configurations. This literature review aims to provide a comprehensive overview of the latest telecommunication system trends and developments in DWDM technology by reviewing existing research and identifying key challenges and opportunities for the research agenda. This review will contribute to advancing knowledge in the field of telecommunication systems especially transmission and configuration to meet the demands of evolving technologies.